Rancang Bangun Sistem Informasi Potensi Pertanian Tanaman Pangan Di Kabupaten Jombang (Studi Kasus: Kecamatan Megaluh) - Santoso, Mayska Widya; Hariadi, Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Agricultural potential is a valuable asset owned by the District Jombang mainly agricultural potential in sub Megaluh. Agriculture is one of the major sectors of the tipping point of regional development. Therefore, the Department of Agriculture District to build an institutional Jombang madiri farmers in collaboration with Agribusiness Sub Terminal which houses and markets all the crops of farmers who are members of the independent farmer. One of the problems that occur in Agribusiness Sub Terminal is the lack of certainty about the availability of food commodities and thus a potential Information system of agricultural crops in the district Jombang who can provide Information in detail. Information is needed about the number of stocks of agricultural commodities dikabupaten megaluh, in an area where STA can get in food crops, food crops are available in each area, whichever area is the highest producer of food crops, as well as who is included in the institutional independent farmers. This Information system will assist in structuring the existing system in which wish Agribusiness Sub Terminal will be able to assist in the management and storage of data in Agribusiness Sub Terminal is particularly associated with the data of institutional farmers. Not only that, it antinya Information system will provide Information about the potential of food crops in sub Megaluh. This system will provide Information needed by the data in the Form of Agribusiness Sub Terminal stock number of agricultural crops, data pests / diseases that attack crops, data infrastructure and the existing infrastructure and the data group of independent farmers. From all these data produced a report containing the agricultural potential of Information increases and decreases in crop production as well as the cause. Agricultural potential report is used by the District Agriculture Office. Jombang to take the best steps in the next growing season. Keywords: Information Systems, Potential of Agricultural, Food Crops.